Self-interest or altruism: Entrepreneurs’ military experience and the motivation of corporate philanthropic donations - Chen, Huaichao; Wu, Huichao; Li, Haiting (Frontiers in Psychology, 2022)
This study aims to explore the motivation of corporate philanthropic donations through investigating the effect of entrepreneurs’ military experience. By drawing upon the data from the 12th Chinese Privately Owned Enterprise (POEs) Survey, this study found that entrepreneurs’ military experience makes a positive effect on corporate philanthropic donations, and that this basic finding keeps consistent after a series of robustness tests. Further, corporate financing constraints do not significantly moderate the relationship between entrepreneurs’ military experience and corporate philanthropic donations, while ROE strengthens the relationship. Therefore, instead of a reduction in philanthropic donations due to the constraints in corporate financing, entrepreneurs with military experience will donate more money when firms achieve better financial performance. The findings suggest that the donations of firms with military entrepreneurs are more likely to be altruistic, enriching the understanding on the motivation of corporations’ philanthropic donations.